2017
DOI: 10.3892/mmr.2017.7982
|View full text |Cite
|
Sign up to set email alerts
|

Oxymatrine induces A549 human non‑small lung cancer cell apoptosis via extrinsic and intrinsic pathways

Abstract: Oxymatrine is one of the primary natural compounds extracted from the Sophora flavescens, and has been reported to exhibit numerous pharmacological properties including cancer‑preventive and anti‑cancer effects, however the mechanisms as to how oxymatrine exhibits anti‑proliferative activity in non‑small cell lung carcinoma cells remains uncertain. The present study aimed to explore the mechanism of its anti‑cancer effect, and whether it is due to apoptosis induction and anti‑migration in the A549 lung cancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Another study showed crude extract of Neosartorya laciniosa KUFC 7896 and Neosartorya tsunodae KUFC 9213 potentiated doxorubicin tumoricidal activity by increasing Dox accumulation in lung cancer nuclei [ 37 ]. Of note, natural compounds such as curcumin and β-asarone from the Chinese herb Acorus tatarinowii [ 38 , 39 ] have showed their tumoricidal activity by reducing the Wnt/β-catenin signaling pathway, by enhancing current chemotherapeutic drugs, for example, curcumin and phloretin [ 40 , 41 ], and by inducing intrinsic or extrinsic apoptotic pathways, including waltonitone, matrine, oxymatrine, astragalin (kaempferol-3- O -β-d-glucoside), and 3- O -α-l-arabinosyl oleanolic acid from Schumacheria castaneifolia Vahl [ 42 , 43 , 44 , 45 , 46 ]. Some natural compounds’ inhibited growth factor have overcome drug resistance, for example, granulatimide, danorubicin, penicinoline, austocystin D, equol, kaempferol, resveratrol, ellagic acid, and butein [ 47 , 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another study showed crude extract of Neosartorya laciniosa KUFC 7896 and Neosartorya tsunodae KUFC 9213 potentiated doxorubicin tumoricidal activity by increasing Dox accumulation in lung cancer nuclei [ 37 ]. Of note, natural compounds such as curcumin and β-asarone from the Chinese herb Acorus tatarinowii [ 38 , 39 ] have showed their tumoricidal activity by reducing the Wnt/β-catenin signaling pathway, by enhancing current chemotherapeutic drugs, for example, curcumin and phloretin [ 40 , 41 ], and by inducing intrinsic or extrinsic apoptotic pathways, including waltonitone, matrine, oxymatrine, astragalin (kaempferol-3- O -β-d-glucoside), and 3- O -α-l-arabinosyl oleanolic acid from Schumacheria castaneifolia Vahl [ 42 , 43 , 44 , 45 , 46 ]. Some natural compounds’ inhibited growth factor have overcome drug resistance, for example, granulatimide, danorubicin, penicinoline, austocystin D, equol, kaempferol, resveratrol, ellagic acid, and butein [ 47 , 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in combination with 5-fluorouracil, OMT can produce a synergistic anti-tumor effect both in vitro and in vivo [55]. Several recent studies have demonstrated the anticancer effects of OMT in diverse cancer cell lines such as prostate cancer [56], ovarian cancer [57], gastric cancer [58], colorectal cancer [59,60,61], breast cancer [62,63], bladder cancer [64], hepatocellular carcinoma [55], esophageal carcinoma [65], osteosarcoma [66,67], cervical cancer [68,69], gallbladder carcinoma [70], laryngeal carcinoma [71], hemangioma [72], lung cancer [73,74,75,76], synovial sarcoma [77], glioblastoma [78,79], and nasopharyngeal carcinoma [80]. The molecular mechanism(s) of action of OMT was found to be mediated by inducing cell cycle arrest and apoptosis and by causing an inhibition of angiogenesis and metastasis [57,64,81,82].…”
Section: Introductionmentioning
confidence: 99%
“…The fluorescent dye, Hoechst 33342, is widely used to stain DNA for evaluating apoptosis of viable cells. It is a blue fluorescent dye that can penetrate cell membranes and is less toxic to cells [ 28 , 29 ]. A small amount of Hoechst 33342 can enter normal cell membranes, so normal cells are light blue.…”
Section: Resultsmentioning
confidence: 99%